1990
DOI: 10.1288/00005537-199002000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The surgical treatment of snoring: A patient's perspective

Abstract: An increasing number of loud snorers seek medical attention because of the social impact of snoring as well as its association with sleep apnea. Uvulopalatopharyngoplasty is reported to reduce or eliminate snoring in the majority of patients; however, little data are available to document the procedure's success. From February 1987 through August 1988, 125 patients underwent uvulopalatopharyngoplasty for habitual snoring; many of these patients had also documented sleep apnea. Of the 74 patients who responded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 5 publications
2
30
0
Order By: Relevance
“…In the literature, we found reference to the best results of UPFP in patients with mild and moderate OSAHS, even though only surgery may not be curative [25][26][27] . IDR < 30 is a predictive positive factor for better results in UPFP 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, we found reference to the best results of UPFP in patients with mild and moderate OSAHS, even though only surgery may not be curative [25][26][27] . IDR < 30 is a predictive positive factor for better results in UPFP 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning snoring, several studies have shown excellent results between 6 months and 1 year, with disappearance of snoring in between 80 and 90% of the cases [34,37,38]. However, recurrences occur with time, probably related to a gain of weight or an increased floppiness of tissues with age.…”
Section: Treatment Of Snoring and Uarsmentioning
confidence: 99%
“…Of the 9 studies reviewed, all but 2 were performed outside the United States. [1][2][3][4][5][6][7][8][9] Jones et al, 2 from the United Kingdom, found that of 193 patients surveyed after UPPP, only 37% perceived a postoperative improvement in sleep quality. Further, only 47% stated that in hindsight would they have undergone surgery.…”
Section: Introductionmentioning
confidence: 99%